1988
DOI: 10.1111/j.1476-5381.1988.tb16578.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐induced contraction of guinea‐pig isolated trachea: studies with novel inhibitors and antagonists of arachidonic acid metabolites

Abstract: 1 Responses of antigen-challenged isolated trachea from sensitized guinea-pigs were pharmacologically characterized by use of some novel inhibitors and antagonists of arachidonic acid metabolites. 2 The cyclo-oxygenase inhibitor, indomethacin, prolonged without altering the maximum response to antigen in the absence of the anti-muscarinic agent, atropine, and/or the Hl-receptor blocker, mepyramine. In the presence of mepyramine, indomethacin both prolonged and increased the magnitude of the response. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…After addition of indomethacin to inhibit cyclo-oxygenase activity, the tracheal tone was reduced and OA-induced contraction potentiated, as already reported (Brink et al, 1981;Jones et al, 1988;Braunstein et al, 1988). In these conditions, GABA was not effective.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…After addition of indomethacin to inhibit cyclo-oxygenase activity, the tracheal tone was reduced and OA-induced contraction potentiated, as already reported (Brink et al, 1981;Jones et al, 1988;Braunstein et al, 1988). In these conditions, GABA was not effective.…”
Section: Discussionsupporting
confidence: 56%
“…From these data the involvement of an endogenous prostanoid in the action of GABA could be proposed. Other explanations cannot be ruled out in view of the fact that indomethacin profoundly affected tracheal responsiveness (Brink et al, 1981;Jones et al, 1988;Braunstein et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study the guinea pig tra cheal preparations were continuously incubated with indomethacin. Jones et al [20] demonstrated the potent inhibitory effect of AA-861 (10 and 30 pM) in tracheal preparations pretreated with indomethacin and mepyramine or atropine and mepyramine, whereas in the ab sence of these chemicals AA-861 was ineffective. Despite the significant differences in the experimental design, the cited studies suggest the important role of cyclooxygenase inhibition on the effects of AA-861.…”
Section: Resultsmentioning
confidence: 99%
“…We used a single dose of antigen (ovalbumin, 1 ¡.ig/ml), a concentration which consistently produced submaximal and reproduc ible responses [17,29] and released considerably large amounts of histamine and leukotrienes [30], the com pounds which are suggested as being the principal media tors of anaphylactic bronchoconstriction in guinea pig [28]. Based on the effects of antihistamines, several stud ies reported the role of histamine in the initial phase of the antigen-induced contraction [28.…”
Section: Discussionmentioning
confidence: 99%